Equation 1) x = 3y - 6
Equation 2) 2x - 4y - 8
Basically, for equation 1, you would move the 3y to the other side so that x and y are on the same side. However, because it is a positive, when moving it over, it becomes a negative.
1) x - 3y = -6
2) 2x - 4y = 8
Multiply ALL of equation 1 by 2 so that you could find the value of y.
1) 2(x - 3y = -6)
1) 2x - 6y = -12
2) 2x - 4y = 8
Subtract equations :)
-2y = -20
Divide both sides of the equation by -2, so that y is isolated.
y = -20/-2
y = 10
Plug in 10 for y in the first equation :)
x = 3y - 6
x = 3(10) - 6
Simplify.
x = 30 - 6
Simplify.
x = 24
So, x = 24, and y = 10
~Hope I helped!~